HIV status of three mining districts of a tribal state in India: Evidence from ICTC data - Ratnesh Sinha; Rozy Raj; Jai Ranjan; Sumegha Rana; Rachna Sharma; Ravi Ranjan Jha; Dewesh Kumar; Umesh Kumar Ojha; Rishabh Kumar Rana (Journal of Family Medicine and Primary Care)
Background: Integrated Counselling and Testing Centre (ICTC) diagnose HIV and STIs early, modifies behavior, reduces vulnerability, and data helps in understanding transmission. Despite having low HIV prevalence, Jharkhand is vulnerable. Post Covid19, HIV has increased. This study examined the prevalence of HIV at ICTC facilities in three mine rich districts of Jharkhand and HIV prevalence as per age, geography, regional, and consequences were examined. Methods: Secondary data analysis was done for 2019–2022 accessible data of ICTC. Totally, 51,062 individual data were examined. Data analysis comprised parametricity testing while data was entered on Excel spreadsheet. Data were summarized using central tendency assessments and Chi-square tests. Logistic regression assessed HIV-positive outcomes and independent variables. P-value < 0.05 was statistically significant. SPSS 29.0 was used for data analysis. Results: Over three years, we recorded 51,508 occurrences, 69% of which were female (35241). Both male and female participants had mean ages of 35.93 ± 14.92 and 27.89 ± 10.67 years, respectively. We found 1.19% HIV prevalence (504/42818) in the ICTC test data. The odds ratio (OR) for HIV positivity was greater in males (3.49, 95% CI: 2.92-4.18) compared to females. HIV prevalence in District Giridih was 4.2% (3.42%-5.26%) with a high risk of HIV positivity (OR 4.24, 95% CI 3.42-5.26). A drop in HIV testing occurred during the COVID-19 lockdown. Conclusions: Since females are flooding ICTC, more targeted interventions, especially for younger women, are needed. Despite their lower numbers, men are at higher risk for HIV.